Some ideological issues of the “Two Customs” Buddhist commandment manuscript ‘Lugs zung gi bslab bya mu thi’ la’i ’phreng ba zhes bya ba bzhugs so” - Damba, Gantemur (Studia Philosophiae Et Juris, 2022)
This paper attempts to study a Buddhist commandment manuscript which have found by two different named by us. “Lugs zung gi bslab bya mu thi' la'i 'phreng ba zhes bya ba bzhugs so” is the famous Buddhist morality commandment writing by Fifth Dalai Lama Ngawang Lobsang Gyatso (1617-1682). It has translated and disseminated by several Mongolian writers & monks. The paper clarifies about this manuscript, its literature research and the main ideology. Here we argue, the “two customs” (moral doctrine for monastic and lay people) as a Buddhist state and religion ideology could be applicable to the modern management ethical concepts. Хоёр ёсыг хосолсон “Улаан сувдан эрхи” хэмээх зохиолын үзэл санааны тухай Энэхүү өгүүлэлд “Хоёр ёсыг хосолсон улаан сувдан эрих” хэмээх нэрт суртгаал оршивой”, “Ёс хоёрын суртгаал сувдан эрих оршуулсан болой” хэмээгдэх хоёр өөр нэртэй гар бичмэлийн тухай болон уг сургаалын талаарх гадаад, дотоод дах судлагдсан байдал ба үндсэн үзэл санааны тухай тодруулах болно. V Далай лам Агваанлувсанжамц (Ngawang Lobsang Gyatso 1617-1682) бээр зохиосон «Улаан сувдан эрих» хэмээх тус сургаалыг монголын мэргэд орчуулж олон нийтийн хүртээл болгож байжээ. Сургаалын үзэл санаа нь буддын номлолыг үндэслэн нийтийн ёс зүйн хэм хэмжээнд тохируулан айлдсан бөгөөд энэ нь өнөөгийн удирдлагын ёс зүйд хамаарах боломжтой. Tүлхүүр үгс: хоёр ёс, буддын ёс зүй, сургаалын үзэл санаа, зам мөр, шашин, төрийн ёс